The voice catchers : how marketers listen in to exploit your feelings, your privacy, and your wallet - Turow, Joseph (Yale University Press, 2021)
The first in-depth examination of the voice intelligence industry, this timely book exposes how artificial intelligence is enabling personalized marketing and discrimination through voice analysis. Amazon and Google have numerous patents around voice profiling, and their smart speakers already extract and use your voice prints for identification and more. Customer service centers are treating you differently from other callers based on what they conclude your voice reveals about your emotions, sentiments, and personality, often in real time. According to scientists, your weight, height, age, race, and illnesses can also be determined from the sound of your voice. Ultimately not only marketers -- but also politicians and governments -- may use voice profiling to infer characteristics about you to serve their interests, not yours or society's.